2019
DOI: 10.1029/2019gl085499
|View full text |Cite
|
Sign up to set email alerts
|

Strong Diffusion of Energetic Electrons by Equatorial Chorus Waves in the Midnight‐to‐Dawn Sector

Abstract: Drastic variations of radiation‐belt/ring current electrons are the result of competing processes of acceleration, transport, and loss. For subrelativistic energetic electrons (10–100 keV), one of the promising loss mechanisms is precipitation into the atmosphere due to pitch angle scattering by whistler mode chorus waves. The efficiency of the scattering has yet to be quantified by direct observations, however. Using in situ measurements by the ERG (Arase) spacecraft in the midnight‐to‐dawn sector at and arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…The electron scattering at 2.9 keV is mostly caused by upper band chorus, and the electron scatterings at 9.3 and 38 keV are mostly caused by LBC. Kasahara et al (2019) examined the energy profiles of the occurrence rates of strong diffusion above several keV, which is roughly consistent with the trend of electron scattering rate at 9.3 and 38 keV due to LBC waves.…”
Section: 1029/2020gl088798supporting
confidence: 56%
“…The electron scattering at 2.9 keV is mostly caused by upper band chorus, and the electron scatterings at 9.3 and 38 keV are mostly caused by LBC. Kasahara et al (2019) examined the energy profiles of the occurrence rates of strong diffusion above several keV, which is roughly consistent with the trend of electron scattering rate at 9.3 and 38 keV due to LBC waves.…”
Section: 1029/2020gl088798supporting
confidence: 56%
“…To remove the dataset possibly related to the plasma sheet phenomena, we discarded the dataset if the angle between the background magnetic field and the model dipole field was >30° (cf., S. Kasahara et al, 2019). Moreover, we only used the dataset obtained outside the plasmapause (L* > 4 and the electron density <30 cm −3 ) to exclude the contribution from plasmaspheric hiss.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Kasahara et al. (2019) reported that the full filling of the loss cones of energetic electrons associated with chorus waves is commonly seen in in‐situ observations. Thus, the positive correlation suggests that the chorus wave growth saturates and/or reaches a strong diffusion limit due to the intense amplitude (Kennel, 1969).…”
Section: Observation Resultsmentioning
confidence: 99%